PELAKSANAAN GERAKAN BERBAGI SANTUNAN SOSIAL DALAM UPAYA PENINGKATAN KEPEDULIAN DI PERUMNAS BERINGI INDAH PERMAI JALAN H. AMIR RT 002 RW 005 KELURAHAN SEI BERINGIN - Yuslizar Yuslizar; Fitri Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
collect funds from the community in the form of infaq funds, alms and community waqf then distribute them to those who are entitled to receive them (dhu'afa people, orphans of the poor) in the form of charity (direct compensation) and empowerment through programs designed with the aim of helping the needs of people's lives dhua'fa to the better. These programs are based on local potential (local sources) that can be run in accordance with the potential and desires of the community in the Perumnas Beringin Indah Permai or Nur'aini prayer room